2016
DOI: 10.5152/jtgga.2016.16053
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a simulation-based training lab on outcomes of hysterectomy

Abstract: Results:The average estimated blood loss before and after simulation-based training was significantly different in TAH and RAH groups (317±170 mL versus 257±146 mL, p=0.003 and 154±107 mL versus 102±88 mL, p=0.004, respectively), but no difference was found for TLH and VH. The mean of length of hospital stay was significantly different before and after simulation-based training for each technique: 3.7±2.3 versus 2.9±2.2 days for TAH, 2.0±1.2 versus 1.3±0.9 days for VH, 2.4±1.3 versus 1.9±2.5 days for TLH, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…19 A positive relationship between systematic training in simulators and reduced operative time and complications were also reported in cases of bariatric and urologic laparoscopic surgery. 29,30 In a Turkish study, Asoglu et al 31 concluded that a simulator lab improves the outcomes of hysterectomy performed at a teaching institution, and may play an adjunct role in developing the resident's surgical skills; the results found by them are in line with the findings of our study.…”
Section: Discussionsupporting
confidence: 90%
“…19 A positive relationship between systematic training in simulators and reduced operative time and complications were also reported in cases of bariatric and urologic laparoscopic surgery. 29,30 In a Turkish study, Asoglu et al 31 concluded that a simulator lab improves the outcomes of hysterectomy performed at a teaching institution, and may play an adjunct role in developing the resident's surgical skills; the results found by them are in line with the findings of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Current evidence suggests that simulation can affect outcomes. 39 Interestingly, it appears that simulation training in the laparoscopic and robotic platforms affect each other. 40 Even more, it appears that improved spatial and temporal eye-brain-hand coordination from video games may improve performance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, with the current evidence of disparities in the use of LH ( 38 ), it is important to determine if it is adequately used for the obese patient population. Finally, there is a clear need to take important clinical variables such as BMI into account when designing and using simulators, which appear helpful in minimally invasive gynecologic surgical training ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%